Analisis Pengelolaan Container Kosong Pada PT. Mentari Mas Multimoda - Johanes Sutanto; Prayonne Adi (Jurnal Titra, 2023)
This study aims to assist PT. Mentari Mas Multimoda in avoiding container shortages and overdue containers that exceed tolerance levels in Surabaya. This particular situation, in which there is frequently a shortage of containers, is not unusual in shipping, including at this company. The company itself has built up a backlog in several of its branches, which is one of the reasons why there aren't enough containers. There are several containers at various MMM locations that are not being managed to be delivered back to the Surabaya headquarters of the business. The overdue container itself is one issue that is brought up by this one. Because they load containers that have the least amount of overdue time in comparison to containers that have been. This is because the stability of containers going in and out can be properly maintained based on existing data. Plans to resolve these issues are formulated in DMAIC.